2007
DOI: 10.1152/ajpcell.00291.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based imaging of sodium iodide symporter activity with the yellow fluorescent protein variant YFP-H148Q/I152L

Abstract: The sodium iodide symporter (NIS) mediates iodide (I(-)) transport in the thyroid gland and other tissues and is of increasing importance as a therapeutic target and nuclear imaging reporter. NIS activity in vitro is currently measured with radiotracers and electrophysiological techniques. We report on the development of a novel live cell imaging assay of NIS activity using the I(-)-sensitive and genetically encodable yellow fluorescent protein (YFP) variant YFP-H148Q/I152L. In FRTL-5 thyrocytes stably express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…YFP-based probes have been successfully used for quantitative screening of chloride transport in different cells (Galietta et al 2001b;Rhoden et al 2007) and for high-throughput screening of Cl-selective glycine and GABA A receptor channels (Kruger et al 2005). Also transgenic mice expressing YFP were generated and used for the analysis of glutamate-induced changes in intracellular Cl and pH (Metzger et al 2002;Slemmer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…YFP-based probes have been successfully used for quantitative screening of chloride transport in different cells (Galietta et al 2001b;Rhoden et al 2007) and for high-throughput screening of Cl-selective glycine and GABA A receptor channels (Kruger et al 2005). Also transgenic mice expressing YFP were generated and used for the analysis of glutamate-induced changes in intracellular Cl and pH (Metzger et al 2002;Slemmer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that FRTL-5/YFP cells cultured in the presence of TSH, respond to 100 µM NaI with a perchlorate-sensitive decrease in YFP fluorescence due to NIS-mediated iodide uptake [31]. Rinsing iodide-loaded cells with iodide-free BSS results in a slow recovery of resting fluorescence due to iodide efflux, complete within 15-20 min (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…A cell line with stable expression of the iodide-sensitive yellow fluorescent protein YFP-H148Q/I152L (FRTL-5/YFP) was used to monitor iodide fluxes [31]. ANO1 gene silencing in FRTL-5/YFP cells was carried out with siRNA directed against rat ANO1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations